Diphylla Ecaudata Spix, 1823 in the Caatinga-Cerrado Ecotone: From Feeding Plasticity to Rabies Propagation in Northeastern Brazil (Global Journal of Medical Research, 2024)
In the Brazilian Northeast the state of Piau exhibits a lacunose chiropteran fauna in terms of diversity Thus knowledge about the ecology of these animals highlighted by the occurrence of significant zoonoses remains abstruse The study aimed to update the geographical distribution of Diphylla ecaudata in the Brazilian Northeast associating it with new foraging approaches and records of the rabies virus in the region For the construction of this work bibliographic searches were conducted in journals and digital platforms reporting the occurrence of Diphylla ecaudata bats in Piau The research included field activities in the municipalities of Picos Pedro II and Milton Brand o setting up mist nets at dusk and dismantling them before dawn in areas suspected of the presence of these animals The captures followed specific protocols cited in specialized literature under authorization 69264-7 SISBio 002 CEUAIFPI 2021 and registration AF78746 in SISGEN
Keywords: brazil; ecotone; bats; piauí; one health